A rare case of coexistence of tuberculosis verrucosa cutis and pulmonary tuberculosis - Huang, Dan; Jin, Shuang; Zhang, Wei; Zhou, Xuyue; Li, Rong; Chen, Kun; Ju, Mei (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
A 52-year-old Chinese builder had presented with pulmonary tuberculosis for more than two decades and asymptomatic painful erythema papules involving the buttocks for one decade. Two decades ago, he was diagnosed with tuberculosis because of haemoptysis, but his tuberculosis had not been treated systematically. A decade later, he had haemoptysis again and began to develop erythema papules on his right buttock and then they spread to the contralateral and perianal areas, but he did not seek any medical treatment. One year ago, the skin lesions deteriorated rapidly and the patient felt pruritus on them and there was purulent fluid after pressing them. There was no improvement of his condition after applying a variety of unknown ointments which the patient purchased himself. He reported no systemic symptoms such as fever, fatigue, night sweat and weight loss during the two decades.